Using the Roy Adaptation Model to Guide Research and/or Practice: Construction of Conceptual-Theoretical-Empirical Systems of Knowledge - Jacqueline Fawcett (Universidad de La Sabana, 2010)
This paper presents an explanation of a three-step process for the use of a conceptual model to guide nursing research and/or practice. Step 1 involves learning the content of the conceptual model and its research and practice guidelines. Step 2 requires a review of literature about the use of the model as a basis for research or practice. Step 3 focuses on construction and communication of a conceptual-theoretical-empirical structure for diverse research topics and practice situations. Emphasis is placed on application of the process to one conceptual model of nursing: the Roy Adaptation Model.